PERBEDAAN SKOR KECEMASAN TAYLOR MINNESOTA ANXIETY SCALE (TMAS) MATERNAL PADA KEHAMILAN DENGAN PREEKLAMPSIA DAN HAMIL NORMAL - Joserizal Serudji; Rizanda Machmud (Universitas Andalas, 2019)
Management of preeclampsia is limited to blood pressure control and symptom relief in combination with close maternal/ fetal surveillance. Until recently, very little attention has been paid to preeclampsia's psychological consequences, especially maternal anxiety. Anxiety disorders can be identified using questionnaires instrument determining anxiety level, the Taylor Minnesota Anxiety Scale (TMAS) questionnaires is one among them. This study aimed to determine the TMAS maternal anxiety score difference between preeclampsia and normal pregnancy. This was an analytical study with a cross-sectional design conducted from March-August 2014 in 40 subjects, consisting of 20 women with preeclampsia and 20 women with normal pregnancy who met the inclusion and exclusion criteria. Anxiety was measured with the TMAS questionnaire. Statistical analysis to determine the TMAS maternal anxiety score difference between preeclampsia and normal pregnancy was t-test. In preeclampsia group, the mean of TMAS maternal anxiety score was 30,45 ± 9,65. While in the normal pregnancy group, the mean of TMAS maternal anxiety score was 18,50 ± 7,62. There was a significant TMAS maternal anxiety score difference between preeclampsia and normal pregnancy (p = 0,000).Keywords: TMAS maternal anxiety score, preeclampsia